An Information System Study of Lim-Es Corporation - Abasolo, Czarina V.; Armena, Agnes A.; Castillo, Michelle B.; Falgui, Jasmin C. (Diliman, Quezon City College of Engineering, 1992)
Structured analysis is used by most large and complex organizations which employ organized procedures. These procedures when executed provide information which support decision making. Moreover, since volumes of transactions are collected, recorded, processed, stored, retrieved and displayed as information, structured specifications are concise, precise, highly readable and more often than not, automated. In contrast, smaller and less complex organizations handle fewer transactions. However, this does not eliminate the need for structured specifications. Structured analysis would be practical and desirable to improve policies and procedures that are not clearly manifested and specify areas for automation and centralization. This study will focus on LIM-ES Corporation, a garments firm owned and operated by Christian Espiritu. Christian Espiritu's designing career started twenty years ago when he decided to specialize his own line of exclusive made-to-order clothes. It was only six years ago that he expanded his operations to include ready to wear or RTW clothes in a team up with ELITE Garments, a clothing firm. He functioned as an in-house designer, and although commissions were paid for his works, he found this to be financially unfulfilling. Since he did not want total involvement, he decided to team up with another garment manufacturer, CHANTEL. Professional differences arose after nine months because he perceived that the company was adopting his personal designs for its own line. In May 1987, he established his own company, the LIM-ES Corporation, for the manufacture of the Christian Espiritu lines for ladies and men. Ever since, his line has been the top grosser in both Shoemart and Castle. The former granted him a place in its Boutique Squares in North EDSA, Cubao and Makati based in his record when he was still in ELITE. The company has since then expanded, having employed other in-house designers whose designs should first merit his approval, and has its own outlets/boutiques at Greenbelt Mall and SM Centerpoint plus a new dealership with LANDMARK. Although the company?s RTW line is doing very well, Mr. Espiritu is still involved in "haute couture". Production for both is housed in building in residential area, Bo. Capitolyo, Pasig, which also holds the main office. The amount of units produced it decided on by applying the Law of Supply and Demand and through conservative projecting. Because of this, ninety five to ninety six percent of total production is sold, resulting in an average sales of P55,000 a month, twenty five percent of which goes to the dealers.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: LIM-ES Corporation; Factory management; Clothing trade; Information resources management